Atherogenic Risk Assessment among Persons Living in Rural Uganda. (22nd June 2016) - Wekesa, Clara; Asiki, Gershim; Kasamba, Ivan; Waswa, Laban; Reynolds, Steven J.; Nsubuga, Rebecca N.; Newton, Rob; Kamali, Anatoli
Abstract : Background . Hypertension and dyslipidemia are independent risk factors for coronary heart disease and commonly coexist. Cardiovascular risk can be reliably predicted using lipid ratios such as the atherogenic index, a useful prognostic parameter for guiding timely interventions. Objective . We assessed the cardiovascular risk profile based on the atherogenic index of residents within a rural Ugandan cohort. Methods . In 2011, a population based survey was conducted among 7507 participants. Sociodemographic characteristics, physical measurements (blood pressure, weight, height, and waist and hip circumference), and blood sampling for nonfasting lipid profile were collected for each participant. Atherogenic risk profile, defined as logarithm base ten of (triglyceride divided by high density lipoprotein cholesterol), was categorised as low risk (<0.1), intermediate risk (0.1–0.24), and high risk (>0.24). Results . Fifty-five percent of participants were female and the mean age was 49.9 years (S D ± 20.2 ). Forty-two percent of participants had high and intermediate atherogenic risk. Persons with hypertension, untreated HIV infection, abnormal glycaemia, and obesity and living in less urbanised villages were more at risk. Conclusion . A significant proportion of persons in this rural population are at risk of atherosclerosis. Key identified populations at risk should be considered for future intervention against cardiovascular related morbidity and mortality. The study however used parameters from unfasted samples that may have a bearing on observed results.